H& H Enterprise: Electronic Coconut Scraper Machine / Norhafizah Ab Jalil - Ab Jalil, Norhafizah (2020)
H&H company introduces a new product called as Electric Coconut Scraper Machine. This product is a modern coconut scraper because it has a plug with copper cable, electric and stainless steel blades and safety control switch power. This electric coconut scraper machine is for domestic use, to shred the coconut faster for everyone. The modern design which is made from fully plastic body and plastic basin for longer life. The price offers are also affordable and users can save time because this is very useful for virgin coconut oil, shredded coconut flakes, coconut milk production etcand. Also very useful in kitchen for cooking traditional foods, as well as residential use.